2022
DOI: 10.3390/su14073750
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 on Wellbeing: Evidence from Israel

Abstract: Many aspects of wellbeing have been studied in the context of the COVID-19 pandemic. However, studies that measure a comprehensive, multi-faceted conceptualization of wellbeing are rare. Using a broad conceptualization of wellbeing, based on the Organisation for Economic Co-operation and Development (OECD) wellbeing indicators and a theoretical model of wellbeing developed previously, this study empirically assesses the wellbeing effects of COVID-19 in Israel. A representative sample of the adult population in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Many nations implemented restrictions on individuals and enterprises in March 2020 to halt the spread of COVID-19, going as far as closing all business operations (Liu et al, 2021;Feitelson et al, 2022). Constraints on economic activity caused a slump, which by historical standards resulted in a sharp rise in unemployment rates (Jena et al, 2021).…”
Section: Covid-19 and The Labor Marketmentioning
confidence: 99%
“…Many nations implemented restrictions on individuals and enterprises in March 2020 to halt the spread of COVID-19, going as far as closing all business operations (Liu et al, 2021;Feitelson et al, 2022). Constraints on economic activity caused a slump, which by historical standards resulted in a sharp rise in unemployment rates (Jena et al, 2021).…”
Section: Covid-19 and The Labor Marketmentioning
confidence: 99%
“…Therefore, people banded together to cooperate and provide each other with assistance to try to return to normal life independently of government policies [28]. Other examples from the recent COVID-19 pandemic have shown that the need for solidarity with and support for those at risk has increased [12].…”
Section: Civic Engagement In Turbulent Timesmentioning
confidence: 99%
“…While civic engagement is one of the more studied topics in political science and public administration, it usually deals with citizens' attitudes or behaviors designed to affect the functioning and stability of communities and governments [10]. It has also been identified as a promoter of improved wellbeing [11,12]. Our main argument is that EOCE is manifested in mutual help, the active support of others, and the overall desire to safeguard communities and societies during emergencies and through their recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Dahlen et al [12] demonstrated a positive and robust association between changes in daily activity levels and corresponding changes in psychological well-being. Feitelson et al [13] assessed the well-being effects of COVID-19 in Israel by analyzing the pandemic's impact on several well-being indicators. Other studies have highlighted the psychological wellbeing of parents and their children.…”
Section: Introductionmentioning
confidence: 99%